A crença no arrebatamento da Igreja: seus desenvolvimentos e transformações imagéticas. - Sebastião, Andréa dos Reis (2010)
The belief in the rapture of the church is part of a fundamentalist eschatological system that is often called premillennial dispensationalism. Its appearance is noted to start in the XIX century through the teachings of Jonh Nelson Darby, a british evangelical preacher founder of the Plymouth Brethren. His teaching incompass the coming of Christ in two steps. One in secret for the church, taking it to heaven and saving it from seven years of tribulation that will follow, the second, a glorious return at the end of seven years for establishment the millennial kingdom on earth, the teaching of Darby were popularized in the footnotes of the Scofield Reference Bible published in 1909 by Cyrus I. Scofield, and it is still set in the eschatological beliefs of the majority of the evangelical fundamentalist churches, both in the EUA and Brazil. In 2002, the film was produced: Left Behind for portraying this belief as well as its update to recent times. However, further study of this belief exposes its doctrinal construct character in which biblical texts from different perspectives of the old and New Testaments are united to form an eschatological framework about to be fulfilled.(AU)